2019
DOI: 10.1097/prs.0000000000005620
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations and Pharmacokinetics of Tranexamic Acid after Two Means of Topical Administration in Massive Weight Loss Skin-Reducing Surgery

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 63 publications
1
32
0
2
Order By: Relevance
“…As topical use is off‐label and the possible local effects of prolonged tissue exposure are largely unknown, keeping drug concentration and contact time as low as possible would be a sensible precaution when advocating routine prophylactic use. Although bolus and gauze administrations may lead to prolonged exposure to TXA, the authors' previous study demonstrated that topical moistening has predictable and swift elimination, as well as rendering systemic concentrations negligible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As topical use is off‐label and the possible local effects of prolonged tissue exposure are largely unknown, keeping drug concentration and contact time as low as possible would be a sensible precaution when advocating routine prophylactic use. Although bolus and gauze administrations may lead to prolonged exposure to TXA, the authors' previous study demonstrated that topical moistening has predictable and swift elimination, as well as rendering systemic concentrations negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The present authors have previously introduced a novel procedure in which the wound surface is simply moistened with 25 mg/ml tranexamic acid before closure, with a mean 39 per cent reduction in drain volume in a small proof‐of‐concept, randomized, placebo‐controlled study of bilateral reduction mammoplasty. Such moistening exposes the wound surface to TXA for a considerably shorter time than topical boluses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topically applied concentration will be diluted by local tissue fluids and the drug will be absorbed gradually. A moistening film will be diluted and absorbed rapidly, representing a limited exposure, whereas a bolus administration into a closed wound cavity will be diluted more slowly and may remain in contact with the wound surface for much longer, representing a chronic exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Topical administration of TXA provides a high concentration at the application site where the antifibrinolytic effect is needed, but a low systemic concentration with an assumed reduced risk of systemic side‐effects. Studies on topical use have been published, particularly from orthopaedic and cardiothoracic surgery, and experience of use in other surgical specialties is increasingly emerging.…”
Section: Introductionmentioning
confidence: 99%